1998
DOI: 10.1111/j.1748-7692.1998.tb00742.x
|View full text |Cite
|
Sign up to set email alerts
|

A Protracted Foraging and Attendance Cycle in Female Juan Fernández Fur Seals

Abstract: Previous studies of fur seals suggest that the attendance patterns and consequent temporal patterning of energy transfer from mother to pup follows a latitudinal cline. While data from subpolar, tropical, and some temperate latitude species support the postulated cline, data for the temperate latitude Juan Fernández fur seal do not. Maternal foraging trips and associated visits ashore were the longest of all otariids studied to date. The first foraging trip postpartum averaged 10.2 d (n= 51 females, range 1–22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 41 publications
7
55
1
3
Order By: Relevance
“…This mode of foraging is, hereafter, referred to as "benthic' foraging. In contrast, lactating fur seals generally undertake longer trips (3-23 days), during which diving is mostly nocturnal (Boyd et al 1991, Francis et aL 1998, Harcourt et al 2001, Beauplet et al 2004). The dives occur in bouts to the deep scattering layer, with a pronounced diel variation in depth that reflects the vertical migration of their prey (Boyd et al 1994, Harcourt et aL 1995, Georges et al 2000a, and foraging occurs mostly in oceanic frontal structures or continental shelf-edges with upwelling regions , This mode of foraging is hereafter referred to as "epipe/agic' foraging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode of foraging is, hereafter, referred to as "benthic' foraging. In contrast, lactating fur seals generally undertake longer trips (3-23 days), during which diving is mostly nocturnal (Boyd et al 1991, Francis et aL 1998, Harcourt et al 2001, Beauplet et al 2004). The dives occur in bouts to the deep scattering layer, with a pronounced diel variation in depth that reflects the vertical migration of their prey (Boyd et al 1994, Harcourt et aL 1995, Georges et al 2000a, and foraging occurs mostly in oceanic frontal structures or continental shelf-edges with upwelling regions , This mode of foraging is hereafter referred to as "epipe/agic' foraging.…”
Section: Introductionmentioning
confidence: 99%
“…Since the development in the mid-19 70s of electronic time-depth recorders (TORs) for measuring diving activity and satellite-telemetry methods for monitoring the at-sea movements of animals, there have been numerous studies investigating the foraging behavior of lactating otariid seals (e,g., Francis et al 1998; Thompson et al 1998;Costa andGales 2000, 2003). There are nine species of fur seals (plus one subspecies) and five species of sea lions (plus one subspecies) (Reijnders et al 1993) and these studies have revealed two broadly divergent patterns for the two groups.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with data of species in which the energy delivery per trip has been studied (Table 6, fur seals: northern, Antarctic, South African, Subantarctic, New Zealand, Galapagos, South American fur seals; sea lions: Steller's and California) (Costa 1991b;Figueroa-Carranza 1994). The 43% fat content of the milk in this species with a mean of 11.5 day foraging trips (Figueroa-Carranza 1994) is similar than that reported for other temperate species that makes long foraging trips, such as the Sub Antarctic fur seal (A. tropicalis) with 42.8% and nine day foraging trips (Georges et al 2001) and the Juan Fernández fur seal 41% with 10 day foraging trips (Francis et al 1998) and it is consistent with the high rates of growth of the pups of these species.…”
Section: Absolutementioning
confidence: 80%
“…According to this theory the females of Guadalupe fur seal that forages at long distance from the rookery with round trips averaging 2,375 ± 1,389 km, and a mean distance to feeding grounds of about 444 ± 151 km from Guadalupe Island (Gallo-Reynoso et (Croxall et al 1985) and northern fur seals (Callorhinus ursinus) which travel 160-200 km (Loughlin et al 1987;Goebel et al 1991) and similar to that of the Juan Fernández fur seal (A. philippii) which travel around 500 km to their feeding grounds (Francis et al 1998). In contrast, Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation